1991
DOI: 10.5636/jgg.43.741
|View full text |Cite
|
Sign up to set email alerts
|

Ground Magnetic Anomalies in the Tanna Fault and Their Implications.

Abstract: The Tanna fault is a left lateral fault extending in the middle of the Izu Peninsula. We carried out a detailed ground magnetic survey at a grid spacing of 50 to 150 m along the Tanna fault and constructed a magnetic model based on the ground survey with the help of drilling data in the Tanna basin and measurement of rock magnetism.Total intensity distribution obtained by the ground magnetic survey represents a distinguished contrast forming relative magnetic highs in the west to the fault and lows in the east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…We thus attempted to apply a small radio-controlled blimp to measure the geomagnetic field at the Tanna Basin located in the northern part of Izu Peninsula. Here we demonstrate that we could successfully obtain magnetic anomaly data comparable with those derived from the ground survey, which had been carried out in the same area by OKUBO et al (1991). Figure 1 shows a schematic diagram of our blimp-borne survey system.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…We thus attempted to apply a small radio-controlled blimp to measure the geomagnetic field at the Tanna Basin located in the northern part of Izu Peninsula. Here we demonstrate that we could successfully obtain magnetic anomaly data comparable with those derived from the ground survey, which had been carried out in the same area by OKUBO et al (1991). Figure 1 shows a schematic diagram of our blimp-borne survey system.…”
Section: Introductionsupporting
confidence: 55%
“…Also a magnetic low can be recognized in the east of the fault. OKUBO et al (1991) suggested that these high magnetic anomalies are caused by the basaltic lava which is located at the depth of 100m under the Tanna Basin sediments. In the south there is a negative anomaly extending from the west to the east.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, Okubo et al (1991) conducted a magnetic survey across the same fault system, but about 4 km to the north of the AMT profile. Their magnetic model, supported by drilling results, shows a significant magnetic contrast across the fault.…”
Section: Discussionmentioning
confidence: 99%
“…Honkura and I §ikara, 1991;Okubo et al, 1991). Such a zone has been interpreted as corresponding to a fractured zone created by repeated displacement of the fault plane, as supported by field evidence (Honkura and I §ikara, 1991).…”
Section: Introductionmentioning
confidence: 76%
“…Brabb and Hanna, 1981;Honkura et al, 1985;I §ikara et al, 1985;Ohshiman et al, 1987;Honkura and I §ikara, 1991;Makino et al, 1991;Okubo et al, 1991;Tuncer et al, 1991a, b). In particular, the examples obtained in the North Anatolian Fault Zone Honkura and I §ikara, 1991) are the most representative ones and the observed anomalies could be interpreted in terms of highly magnetized dike-like bodies lying along the active faults (I §ikara et al, 1985).…”
Section: Introductionmentioning
confidence: 99%